Food cue recruits increased reward processing and decreased inhibitory control processing in the obese/overweight: An activation likelihood estimation meta-analysis of fMRI studies. Issue 2 (March 2020) - Meng, Xia; Huang, Duo; Ao, Hua; Wang, Xinyu; Gao, Xiao
Highlights: People with obesity shows greater response to food cues in visual-attention related areas. High calories food induced greater activation in reward areas in people with obesity. Healthy weight group shows greater response to food cues in gustatory area. Greater inhibitory control for food cues is elicited in healthy weight group. Abstract: Introduction: Growing researches have shown that obese/overweight and healthy weight individuals exhibit different neural responses to food-related stimuli. Accordingly, researchers proposed several theories to explain these differences. Hereon, meta-analyses were conducted using activation likelihood estimation (ALE) to verify these theories and specify the reason of overeating from two aspects. Materials and Methods: Pubmed, Web of Science and Neurosynth were searched for the current study and screened according to inclusion criteria. Firstly, neural responses to visual food cues versus non-food images were compared between obese/overweight and healthy weight individuals. Then, neural activation to high-calorie food images versus low-calorie food/non-food visual stimuli was further investigated among the two populations. Coordinates in included studies were recorded and analysed by Ginger ALE software under threshold at uncorrected p < 0.001 with cluster-level p < 0.05 (cFWE). Results: Eleven and seven studies were found in the first and second set of meta-analysis, respectively. The first meta-analysis showed that obese/overweight have hyper-responsivity in reward area and hypo-responsivity in both gustatory processing and inhibitory control area. The second meta-analysis indicated that the reward responsivity in the obese/overweight individuals was amplified and healthy weight individuals had higher activation in areas associated with gustatory processing in response to high-calorie food images. Conclusions: Our results showed that the obese/overweight exhibit hyper-responsivity in brain regions involved in reward processing for visual food cue which provide strong support for incentive-sensitization theory of obesity and healthy weight individuals showed higher response in inhibitory control region which support the inhibitory control deficit theory of obesity.